Indonesia’s Patent Policy on the Protection of Genetic Resources related Traditional Knowledge; Is it a Synergy to Fulfill the TRIPs agreement and CBD Compliance? - Nurul Barizah (Yuridika, 2019)
This research analyses the compatibility of Indonesian Patent Act with the Trade related Aspect of Intellectual Property Rights (TRIPs) Agreement and the Convention on Biological Diversity (CBD) dealing with Genetic Resources Related to Traditional Knowledge (GRTK). The focus this analyses on whether the new Indonesian Patent Act provides a clear policy on the protection of GRTKF and the development of the biotechnology in Indonesia, particularly on the patentability of genetic resources related inventions, including genes patent. This research found that the new Indonesian Patent Act on GRTK is not only to synergise between the TRIPs Agreement obligation and the CBD compliance, but also adopted patent policies derived from other developed countries particularly in examining the patentability thresholds and exceptions from patentability. Even, in the context of patentability of living organisms, Indonesia adopts a very liberal approach compared to most industrialised countries. This research advises that Indonesian patent policy on GRTK should take into account the richness of this country on biodiversity and the level of biotechnology industry development.